L'ontologia della persona : il dualismo mente-corpo nella proposta di E. J. Lowe - Tambassi, Timothy (Sapientia, 2013)
The aim of this paper is to analyze E.J. Lowe’s thesis on mind-body relation and his ontology of personhood. In the first paragraph I highlight what Lowe means by philosophy of mind and the relationship between philosophy of mind, metaphysics, and ontology. In the following three I focus on the contemporary debate on mind-body relation, on Kirk Ludwig’s classification, and on Lowe’s positions. In the next four paragraphs I discuss Lowe’s theses regarding persons and their bodies, his ontology of personhood and of persons as a simple substance, and themes like perception, action and biological evolution. Finally, I will show the advantages of Lowe’s position in respect to Cartesian substance dualism.